Management of complex ventral hernias: results of an international survey. Issue 1 (11th February 2021) - Knaapen, L; Buyne, O; Slater, N; Matthews, B; Goor, H; Rosman, C
Abstract: Background: The surgical treatment of patients with complex ventral hernias is challenging. The aim of this study was to present an international overview of expert opinions on current practice. Methods: A survey questionnaire was designed to investigate preoperative risk management, surgical approach and mesh choice in patients undergoing complex hernias repair, and treatment strategies for infected meshes. Geographical location of practice, experience and annual volumes of the surgeons were compared. Results: Of 408 surgeons, 234 (57.4 per cent) were practising in the USA, 116 (28.4 per cent) in Europe, and 58 (14.2 per cent) in other countries. Some 412 of 418 surgeons (98.6 per cent) performed open repair and 322 of 416 (77.4 per cent) performed laparoscopic repair. Most recommended preoperative work-up/lifestyle changes such as smoking cessation (319 of 398, 80.2 per cent) and weight loss (254 of 399, 63.7 per cent), but the consequences of these strategies varied. American surgeons and less experienced surgeons were stricter. Antibiotics were given at least 1 h before surgery by 295 of 414 respondents (71.3 per cent). Synthetic and biological meshes were used equally in contaminated primary hernia repair, whereas for recurrent hernia repair synthetic mesh was used in a clean environment and biological or no mesh in a contaminated environment. American surgeons and surgeons with less experience preferred biological mesh in contaminated environments significantly more often. Percutaneous drainage and antibiotics were the first steps recommended in treating mesh infection. In the presence of sepsis, most surgeons favoured synthetic mesh explantation and further repair with biological mesh. Conclusion: There remains a paucity of good-quality evidence in dealing with these hernias, leading to variations in management. Patient optimization and issues related to mesh choice and infections require well designed prospective studies. Abstract : This survey provided a good overview of current practice among difficult subjects in ventral hernia repair on which limited guidelines exist in two continents (Europe and USA). Based on the findings, the authors recommend that more attention should be paid to preoperative optimization, specifically preoperative diabetic control and adequate antibiotic prophylaxis. Prehabilitation programmes should be implemented together with patient education on the importance of risk reduction and the impact of complications. Reaching goals set to optimize patients before hernia surgery should be a quality control parameter. The use of biological mesh in ventral hernia repair should be appraised critically. To improve adherence to guidelines and protocol decision tools, guideline training, easy ways of data-sharing, feedback loops and apps may be helpful.